Effectiveness of GeneXpert® in the diagnosis of tuberculosis in people living with HIV/AIDS - Mariana Gaspar Botelho Funari de Faria; Rubia Laine de Paula Andrade; Ana Julia Gonçalves Camillo; Karina Fonseca de Souza Leite; Nanci Michele Saita; Valdes Roberto Bollela; Carlos Eduardo Menezes de Rezende; Aline Aparecida Monroe (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To identify and synthesize the scientific knowledge produced regarding the effectiveness of the GeneXpert test in the diagnosis of pulmonary tuberculosis (TB) in people living with HIV/AIDS. METHODS Integrative literature review, which was searched on Embase, Scopus, PubMed, Cinahl, Academic Search Premier, Socindex, and LILACS platforms, in December 2019. The studies surveyed went through two stages of selection: reading of titles and abstracts by two reviewers independently; using the Rayyan platform and reading. Nineteen primary studies in English, Portuguese, and Spanish that answered the study's guiding question were included: How effective is the GeneXpert test in the diagnosis of pulmonary TB in people living with HIV/AIDS? RESULTS The use of GeneXpert substantially increased the detection of TB cases among the population co-infected with HIV/AIDS, with sensitivity ranging from 68% to 100%, superior to sputum smear microscopy. Specificity ranged from 91.7% to 100%; the positive predictive value from 79.2% to 96.1%; and the negative predictive value from 84.6% to 99.3%. These values were considered similar to sputum smear microscopy by most studies. We also compared these results with different ways of performing culture and other molecular tests, being considered inferior only to the Xpert Ultra. CONCLUSION It is possible to affirm that places with a high incidence of HIV/AIDS would benefit from the implementation of the GeneXpert test, entailing effectiveness in diagnosing pulmonary TB in this population when compared to sputum smear microscopy, a widely used test for detection of cases.